(untitled) (Research, Society and Development, 2020)
Behavioral Skills Training (BST) represents an effective and efficient approach to train staff in implementing Applied Behavior Analysis (ABA) interventions to learners with Autism Spectrum Disorder (ASD), with the purpose of reducing undesirable behaviors and establishing more appropriate ones. It comprises the following components: (1) instructions on ABA basic principles, regarding the teaching of behavior targets; (2) modeling, with demonstration of behaviors to be emitted during the teaching; (3) behavioral rehearsal with a confederate; and (4) performance feedback. The goal of the current research was to evaluate the effects of BST training on the establishment of repertoires, in four undergraduate Psychology interns, to teach nonverbal (audiovisual pairing and motor imitation) and verbal (labeling and answering questions) skills to a confederate, who pretended to act like a child with ASD. Thereafter, it was also a goal to assess generalization of the teaching to a real child with ASD. The participants were unfamiliar with ASD and ABA, but the results of the study suggested that BST improved accuracy during the teaching of targets to the confederate. In baseline, the percentage of accuracy per participant were the following: P1 (4.55%); P2 (9.73%); P3 (13.76%); P4 (22.29%). All participants reached criterion when BST, with both immediate and delayed feedback, was implemented. Performance accuracy was above 90% for all. In the end, generalization probes were conducted during the teaching of targets to a real child with ASD, and performance accuracy was also above 90%.